Development of Computational Physics Practical Instructions: Visualization of the Laplace Equation Phenomenon - Etik Irawati; Hartono Hartono; Sulhadi Sulhadi (Physics Communication, 2025)
Practical instructions for practical activities in computational physics courses have been successfully developed with material on the Laplace equation for temperature distribution. This research aims to produce practical instructions and determine the characteristics, feasibility, and responses of students to practical instructions for computational physics on the Laplace equation. The research design used is development research or R&D (Research and Development) which was modified from Sugiyono. The research was carried out at the Computer Laboratory of PGRI University Semarang with Physics Education study program students as research subjects. The research results show that the computational physics practicum instructions developed have the criteria "Very Feasible" based on validation from three computational physics experts with respective percentages of 96%, 99% and 93%. The characteristics of this computational physics practical guide are that it is prepared using computational thinking techniques and written using structured documents (LaTex), presented explicitly and equipped with algorithms, solving with two different scenarios (iterations and matrices) in one case as well as writing coding. uses the latest software (Python) and is equipped with algorithms. This computational physics practical instruction received a very good response from students with a percentage of 87% in the initial trial and 88% in the usage trial.